Crystal Lakes Firewise Task Force - State Fire Assistance - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2013)
Located in: Fort Collins office files. Crystal Lakes Firewise Task Force records related to their Colorado State Forest Service (CSFS) State Fire Assistance (SFA) program. Includes: payment and reimbursement requests submitted by the Crystal Association; reimbursement calculation worksheets; invoices; statements; receipts; cost documentation; financial assistance program cooperative match project summary and scope of work report; grant application; correspondence to include printout of emails; annotated map; and photographic prints of mitigation before and after.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado